ENHANCING PROFESSIONAL LEXICAL ACCURACY THROUGH SELF- AND PEER-ASSESSMENT IN PROJECT-BASED LEARNING: EVIDENCE FROM MICE EDUCATION - Tantri Sari Safitry; Elitaria Bestri Agustina Siregar; Dhimas Ghozy Arrasy; Djuni Akbar; Septina Indrayani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The investigation of the classroom-based action research revolves around self-assessment and peer-assessment and their significance in enhancing the lexical precision and diversity in students enrolled in the English class for MICE study program. The research is focused on the Assessment for Learning (AfL) framework and the country's Lexical Competence Theory. The students were allowed to communicate and express their ideas through various authentic tasks such as sales pitch presentations and event proposal pitching, all of which were designed within a Project-Based Learning (PjBL) context. Vocabulary assessment rubrics, self-reflection forms, and video recordings of students’ project presentations were used to gather data. The sequence of the research was split into two project cycles, facilitating continuous reflection and improvement. The result shows that through the use of self and peer assessments, students will not only become more conscious of their lexical choices and accuracy but also take charge of their learning. This research is significant for the domain of English for Specific Purposes (ESP), especially for MICE learning, since it shows how reflective assessment methods in PjBL can remarkably change the lexical skills and communicative confidence of students in professional scenarios.